Preparation of Palygorskite hybrid iron oxide red pigment and its application in waterborne polyurethane composite coatings and ceramics. (1st June 2022) - Han, Yisen; Shan, Miao; Lu, Yunfei; Liu, Songqin
Abstract: Palygorskite (Pal) is a kind of magnesium aluminum silicate clay mineral with a one-dimensional rod and layer chain structure. Herein, Pal hybrid iron oxide red pigment (Pal/ α -Fe2 O3 ) was prepared by the grinding method. Pal acted as a matrix to fix α -Fe2 O3 particles and influenced the performances of composite pigments by changing the particle size and distribution of α -Fe2 O3 . The color difference analysis showed that the color performances of composite pigments were closely related to the ratio of Pal to α -Fe2 O3 . Compared with the original red iron oxide pigment, the tinting strength of the composite pigment was increased by about 15%. When Pal/ α -Fe2 O3 was used as the red pigment for coating, it had good storage stability for waterborne coating and improved its adhesion and corrosion resistance. Pal/ α -Fe2 O3 composite pigments had excellent high-temperature resistance, which could increase the calcination temperature of ceramic pigments and would be beneficial for the ceramic industry. The synthetic method of Pal/ α -Fe2 O3 composite pigment was simple, low-cost, and environmentally friendly, and could be applied to large-scale industrial production.